The humility of the Eternal Son "reformed" kenoticism and the repair of Chalcedon - McCormack, Bruce L. 1952- (Cambridge University Press, 2021)
"the "person" of Christ. In this eagerly-awaited volume - the result of deep and sustained reflection - distinguished theologian Bruce McCormack examines the reasons for this philosophical and theological failure. His book serves as a critical history that traces modern attempts at resolution of this problem, from the nineteenth-century Lutheran emphasis on Kenoticism (or the 'self-emptying' of the Son in order to be receptive to the will of the Father) to post-Barthian efforts that evade the issue by collapsing the second person of the Trinity into the human Jesus - thereby rejecting altogether the logic of the classical 'two-natures' Christology. McCormack shows how New Testament Christologies both limit and authorize ontological reflection, and in so doing offers a distinctively Reformed version of Kenoticism. Proposing a new and bold divine ontology, with a convincing basis in Christology, he persuasively argues that the unity of the "person" is in fact guaranteed by the Son's act of taking into his "being" the lived existence of Jesus"--
Includes bibliographical references and index
Keywords: Inkarnation Jesu; Jesus Christ / History of doctrines; Jesus Christ / Humiliation / History of doctrines; Incarnation / History of doctrines